Annihilation of positrons in hydrogen-saturated titanium - Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Boev O. V.; Imas O. N.; Lider A. M.; Surkov A. S.; Chernov I. P. Ivan Petrovich (2003, 2003)
The effect of atomic hydrogen on the electronic structure of α-titanium samples is studied using the electron-positron annihilation methods. It is shown that different states of hydrogen atoms are manifested in different ways in the positron lifetime distribution spectrum. The results of theoretical calculations of the first component of the positron lifetime are in accord with the obtained experimental data.